Negative Binomial Regression Modeling in the Analysis of Malnourished Under-Five Children in Central Java in 2023 - Bayu Aji Bachtiar; Udin Erawanto (JOSAR (Journal of Students Academic Research), 2025)
Toddlers in Indonesia are an age group that is vulnerable to the impacts of malnutrition. Central Java Province is the province with the highest number of cases of malnutrition in toddlers in Java, namely 9525 cases of malnutrition during 2023. This study aims to analyze the variables that influence malnutrition in Central Java Province in 2023. The data used are secondary data in 2023sourced from the Badan Pusat Statistik (BPS), Central Java Provincial Health Service, and Badan Panga Nasional (BPN). The analysis method used is negative binomial regression for modeling enumeration data to overcome the problem of overdispersion in Poisson regression. The results of the analysis show that there is a negative influence of the variables of the percentage of households with access to proper sanitation, the food security index, and the percentage of babies receiving exclusive breastfeeding on the number of cases of malnutrition in toddlers. Meanwhile, the proportion of women aged over 15 years who have a maximum junior high school diploma has an effect on increasing cases of malnutrition in toddlers.